Perception and reason - Brewer, Bill, Dr (Clarendon Press ; Oxford University Press, 1999)
This volume presents an original view of the role of conscious experience in the acquisition of knowledge. It argues that experiences must provide reasons for beliefs if there are to be any beliefs about the mind-independent world at all.